Novel Variation and Evolution of AvrPiz-t of Magnaporthe oryzae in Field Isolates - Wang, Qun; Li, Jinbin; Lu, Lin; He, Chengxing; Li, Chengyun (Frontiers in Genetics, 2020)
The avirulence (Avr) genes of Magnaporthe oryzae are recognized by the cognate resistance (R) genes of rice and activates immunity to rice mediated by the R gene. The high degree of variability in pathogenicity of the isolates of M. oryzae makes the control of rice blast difficult. The ability to defeat the R gene has been hypothesized to be due to the instability of Avr gene in M. oryzae. Further study on the variation of the Avr genes in naturally-occurring field isolates of M. oryze may yield valuable information for the deployment of R genes in rice production areas. AvrPiz-t and Piz-t are a pair of valuable genes in the Rice-Magnaporthe pathosystem. AvrPiz-t is recognized by Piz-t and determined the effectiveness of Piz-t. For effectively deploying R gene Piz-t, the distribution, variation and evolution of the corresponding Avr gene AvrPiz-t were proceeded among 312 M.oryzae isolates collected from Yunnan rice production areas of China. PCR amplification and pathogenicity assay of AvrPiz-t showed that 202 isolates (64.7%) held AvrPiz-t alleles and were avirulent to IRBLzt-T (holding Piz-t). There were 42.3-83.3% avirulent isolates containing AvrPiz-t among seven regions in Yunnan Province. Meanwhile, 11 haplotypes of AvrPiz-t encoding three novel AvrPiz-t variants were identified among 100 isolates. A 198bps insertion homologous to solo-LTR of the retrotransposon inago2 in promoter region of AvrPiz-t in one isolate and a framshift mutation of CDS in another isolate were identified among 100 isolates, and those two isolates were evolved to virulent from avirulent. Synonymous mutation and non-AUG-initiated N-terminal extension keep AvrPiz-t gene avirulence function in M.oryzae field isolate of Yunnan. Haplotype network showed that H3 was ancestral haplotype. Structure variance for absence (28.2%) or partial fragment loss (71.8%) of AvrPiz-t was founded among 39 virulent isolates and may cause AvrPiz-t avirulence function to be lost. In all, the AvrPiz-t evolved to virulent from avirulent forms via point mutation, retrotransposon, shift mutation and structure variance under field conditions.